A model of employee engagement: Integrating the job demands-resources model and Kahn's psychological conditions - Masanque, Merwin R. (Animo Repository, 2021)
The research purpose was to examine the underlying mechanism between the relationship of job resources with employee engagement. The research proposed that job resources influence employee engagement through the mediating role of psychological meaningfulness, psychological safety, and psychological availability. The research participants were full-time employees from different industries and had been working for their current employer for at least one year. A non-experimental, cross-sectional, explanatory research design was implemented. An online survey was given to the participants to measure autonomy as a job resource, psychological conditions, and employee engagement. All instruments were adapted from previous studies (Johari, Che Mit & Yahya, 2009; May, Gilson & Harter, 2004). Mediation analysis was used to examine the data through Model 6 of the PROCESS Macro in SPSS developed by Hayes (2013). The research followed Kahn’s theory of engagement and integrated it with the job demands-resources model — a widely used theory in engagement research. Results show that Kahn’s psychological conditions of meaningfulness and safety mediated the relationship between autonomy and employee engagement.